Development and Application of a Risk Assessment System in Determining Individuals' Susceptibility to Developing Type II Diabetes Mellitus: A Quantitative Study in a Selected Community in Angeles City - Banate, Ivan Gezumi C.; Arceo, Alyssa Monique S.; Canlas, Princess Anne M.; Cope, Danica Mae C.; Eyog, Kristine Noeme G.; Garcia, Ellyna Ussiel C.; Magsino, Juliana Rojin D.; Nagum, Iris Lindsay Q.; Nolasco, Jamaica Zoe B.; Salas, Simon Albert Y.; Sunga, Dylan M.; Lopez, Rolando L.; Bingcang, Angelli Krizka D. (Celebes Nursing Journal, 2025)
Introduction: The incidence of type 2 diabetes mellitus (T2DM) continues to rise worldwide, with many individuals remaining undiagnosed until complications develop. Standard diagnostic procedures are effective but often costly and inaccessible in community settings, causing delays in early detection and management. Objective: This study aimed to develop and apply a digital risk assessment system to identify individuals at risk of developing T2DM in a selected community in Angeles City. The system was designed as a cost-effective, non-invasive, and nurse-led screening tool to support early prevention and promote proactive health initiatives within the community. Methods: A cross-sectional descriptive design was conducted in two phases following approval from the Ethics Review Committee. Phase 1 involved system development and evaluation by community health nurses using a 16-item questionnaire. Phase 2 involved applying the system to 372 community residents using another 16-item questionnaire to generate individual risk profiles. Data were analyzed using percentage, frequency, mean, and standard deviation. Results: The system achieved “best imaginable” ratings in usability, information quality, and interface design, demonstrating its appropriateness for community application. Risk distribution showed that 42.74% of respondents were at low risk, 37.37% slightly elevated, 10.48% moderate, 8.60% high, and 0.81% very high risk for T2DM. Conclusion: The developed system offers a non-invasive, low-cost tool for identifying T2DM susceptibility and empowering early preventive action. Integrating such tools into nursing practice can enhance community screening programs, guide tailored health education, and strengthen primary health care. Raising awareness of personal susceptibility is vital to fostering proactive health behaviors, reducing disease burden, and advancing community-based nursing interventions.